Resistive switching behavior of partially anodized aluminum thin film at elevated temperatures - Zhu, Wei (2013)
Resistive switching behavior of partially anodized aluminum thin film has been investigated at temperatures of 25 °C–250 °C. Both the reset and set voltages decrease with increasing temperature, showing Arrhenius-like dependence with small activation energies. The pulse voltage experiment also suggests that the conductive filament breaking/reconnection is easier to occur at a higher temperature. Some possible mechanisms for the phenomena are discussed. On the other hand, at elevated temperatures without continuous electric field applied, while the high-resistance state exhibits no significant change with time, the low-resistance state (LRS) shows a continuous degradation, and there is a sudden failure. The LRS failure time shows Arrhenius dependence with an activation energy of ~1.3 eV, suggesting that the LRS failure could be due to the migration of the excess Al atoms at high temperatures.